Integrating Technology into Accounting Education: A Grounded Theory Study on the Use of Accounting Software in Practicum Classes - Rohman, Abelia Fajroyur; Soraya, Ayya; Maulida, Wulan Nur; Kustiwi, Irda Agustin (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
This study aims to explore how technology, particularly accounting software, is integrated into accounting education through practicum- based learning. Using a grounded theory approach, the research investigates students' and instructors’ perceptions, experiences, and challenges in utilizing computerized accounting systems during practical sessions. Data were collected through in-depth interviews, observations, and document analysis involving accounting students and educators from selected higher education institutions. The findings reveal key themes related to digital readiness, pedagogical adaptation, software usability, and professional skill development. A theoretical model is proposed to illustrate the process of technology integration in accounting education, highlighting both facilitating factors and obstacles. This study contributes to a deeper understanding of how accounting education can align with the demands of digital transformation in the financial industry.